Giant Multilocular Prostatic Cystadenoma in a 14-Year-Old Male: A Case Report of a Pediatric Pelvic Mass. (May 2022) - Quiring, Mark; Berry, Stacey; Uffman, John; Pinto, Kirk; Kaye, Jonathan
Giant multilocular prostatic cystadenoma (GMC) is an extremely rare, benign tumor seen in both adult and pediatric males. The neoplasm originates from prostatic tissue and is typically found within the rectovesical pouch, varying in both size and morphology. Microscopically, GMC contains both glandular and cystic prostatic tissue lined by cuboidal and columnar epithelium. Symptoms often arise once the pelvic mass begins to obstruct the surrounding structures and organs, although invasion into surrounding tissue is unlikely. Common symptoms include abdominal pain, urinary retention, and dysuria. The standard treatment for GMC is surgical removal of the mass with good outcomes and only 1 known case of recurrence. Here we present the case of a 14-year-old male with GMC—the youngest patient reported to date—who presented with abdominal pain, difficulty voiding, and hydroureteronephrosis.